Картографо-інформаційне забезпечення активного туризму в Українських Карпатах - Бучко, Жанна Іванівна (Чернівці: Рута, 2009)
Problems of cartographic and informational support of action tourism in the Ukrainian Carpathians are substantiated. The support of tourist trails with appropriate ethnographic literature and cartographic materials is considered. We analyze the maps and other printed products that produced for the Carpathian tourism. Proposals of rational use of cartographic and informational support of action tourism are offered. It offers information of natural and historic peculiarities of the Carpathians region, interesting settlements, main travel organizations that possess real potential for arranging amateur sport and commercial tours.
Cartographic and informational support of action tourism in the Ukrainian Carpathians
Keywords: Туристичний маршрут; Карта; Картосхема; Активний туризм